On some mixed variational principles in electro-elastostatics - Vogel, Franziska Anna; Bustamante, Roger A.; Steinmann, Paul (International Journal of Non-Linear Mechanics, 2012)
Some mixed variational principles are presented for problems involving electro-elastic interactions, whereby the electric field follows from a scalar potential. Firstly, in order to set the stage, we consider the basic case of merely free space. Secondly, to increase the complexity, we immerse an electro-active but mechanically rigid body into vacuum. As our final goal we thirdly treat a geometrically non-linear deformable electro-elastic body that is surrounded by free space. Electro-elastic bodies are of particular interest since they can develop large elastic deformations as a response to the presence of electric fields. © 2011 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.tech.FT.FT-TM.onsome_9
Keywords: Continuum mechanics; Electrostatics; Mixed principles